Towards the synthesis and delivery of a halogenated MCT1 substrate - Skaripa-Koukelli, Eirini (2019)
The monocarboxylate transporter 1 (MCT1) has received special attention as a potential therapeutic target in cancer thanks to its role in lactate shuttling. In breast cancer (BC), high MCT1 expression has been correlated with basal-like phenotype and a ‘triple-negative’ status, an aggressive subgroup of tumours with no identified molecular targets.